2022
DOI: 10.3390/ijerph19063430
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Types of Service Providers on Experience Economy, Brand Attitude, and Brand Loyalty in the Restaurant Industry

Abstract: This study was designed to understand the relationships among the experience economy, brand attitude, and brand loyalty based on the type of service providers, such as robot servers and human servers in the restaurant industry. The data were collected from 296 people who experienced robot servers and from 294 people who experienced human servers and was analyzed through structural equation modeling (SEM), which indicated that the four sub-dimensions of the experience economy: education, entertainment, esthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…Eventually, CSR helps to improve the relationship between employees and their employers. Previous studies [36,37] have indicated that CSR has excellent potential to increase customer satisfaction and loyalty. As a result, most businesses include it as an essential component of their business strategy [5].…”
Section: Corporate Reputation and Corporate Social Responsibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Eventually, CSR helps to improve the relationship between employees and their employers. Previous studies [36,37] have indicated that CSR has excellent potential to increase customer satisfaction and loyalty. As a result, most businesses include it as an essential component of their business strategy [5].…”
Section: Corporate Reputation and Corporate Social Responsibilitymentioning
confidence: 99%
“…Companies must be actively involved in CSR activities to build and recover trust [46]. Vigorous CSR activities influence employees' perceptions and attitudes toward the company [37]. Enhancing workplace trust between employees and managers can lead to better outcomes for both parties [20].…”
Section: Organizational Trust and Corporate Social Responsibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Social circle is also considered while studying depression in teenagers ( 69 71 ). The traditional Pakistani culture emphasizes collectivism and peace and focuses on blood relations and sensitive sentiments.…”
Section: Theory and Literaturementioning
confidence: 99%
“…In the modern, highly competitive business environment, organizational performance is influenced by several internal and external factors [ 1 ], such as infrastructure and facilities, financial stability, and human capital [ 2 ]. A number of researchers, for example, Pinto and He [ 3 ] and Habib et al [ 4 ], have termed human capital as the most important element in the success or failure of any business.…”
Section: Introductionmentioning
confidence: 99%